Empirically testing the mediating effect of distributive justice in the relationship between adequacy of benefits and personal outcomes - Azman Ismail; Antonia Girardi; Ali Boerhannoeddin (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2009)
This study was conducted to examine the effect of adequacy of benefits and distributive justice on personal outcomes (i.e., job satisfaction and organizational commitment) using 583 usable questionnaires gathered from Malaysian public institutions of higher learning (PLEARNINGINSTITUTE sector). The outcomes of step-wise regression analysis showed that the inclusion of distributive justice in the analysis has increased the effect of adequacy of benefits on both job satisfaction and organizational commitment. Furthermore, the findings of this study confirm that distributive justice do act as a partial mediating variable in the benefits program models of the organizational sector sample. In addition, implications and limitations, as well as directions for future research are discussed.
Keywords: 330; Adequacy of Benefits; Distributive Justice; Personal Outcomes